Nonlinear static pushover Analysis of a two story Reinforced Concrete Building (Case study) (Journal of Civil Engineering Researchers, 2017)
Iran plateau lies in a high seismic zone and very seismic events of magnitude 6 or greater were recorded in long term period of last times. historical events involving ground cracking and fissuring with faults displacement took place in last years. The recent seismic events have led to concerns on safety and vulnerability of RC buildings, which were most designed for gravity and limited lateral loads in the past devoid of any ductile detailing of joints. This paper presents a 3D nonlinear static analysis for seismic performance evaluation and assessment in the form of capacity curve of an existing two-story reinforced concrete frame building .The building have columns with fixed supports at base, reinforced concrete frame and flat slab systems at different floor levels. The seismic displacement response of the RC frame building is obtained using the 3D pushover analysis. The 3D static pushover analysis was carried out using SEISMOSTRUCT incorporating inelastic material behavior for concrete and steel. Moment curvature and P-M interactions of frame members were considered in software. The damage modes includes a sequence of yielding and failure of members and structural levels were obtained for the target displacement expected under design earthquake.
Keywords: Reinforced concrete; pushover analysis; plastic hinges; response spectra; capacity curve